Efektivitas Iklan Televisi Indomie Versi Ayam Geprek Hype Abis - Bintang Paramiditha, I Gusti Agung Istri; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Advertising is a marketing communication activity aimed at the public by using advertising as  message s to promote goods, services, and ideas. This study aims to examine the effectiveness of the advertisement of Indomie Ayam Geprek Hype Abis on the television. This study uses  descriptive quantitative approach involving 120 respondents who were determined by purposive sampling. Data were collected using questionnaires distributed through google forms to capture respondents' perceptions and measured by Likert Sca I e. The data ana I ysis technique in this study used EPIC (Empathy, Persuasion, I mpact, Communication) Model. The results showed that the four dimensions of EPIC Model were in the range scale of effective. Among the four dimensions, it was found that the persuasion dimension got the lowest average value. Indomie company management is advised to develop advertising with more attention to the dimension of persuasion through emphasis on the advantages and benefits of the advertised product.   Key W ords: Indomie Ayam Geprek Hype Abis, Advertisement Effectiveness, EPIC Model